The Relationship of Nurse Therapeutic Communication with Anxiety among Rheumatoid Patients - Asep Gunawan; Nadya Salsabilla; Fitriani Fajriah; Nurshofi Intansari; Haryani; Maulidah Noor Sofia; Noneng Nuraida; Ikna Cahyadi Kurniawan (Genius Journal, 2022)
Objective: This study uses a descriptive correlational quantitative method with a cross-sectional approach to determine whether there is a relationship between therapeutic communication and anxiety in rheumatic patients at the Jatinagara Health Center. Method: This study uses a descriptive correlational quantitative method with a cross-sectional approach to determine whether there is a relationship between therapeutic communication and anxiety in rheumatic patients at the Jatinagara Health Center. The population in this study were rheumatism sufferers as many as 119 people in the Jatinagara Health Center area using accidental sampling technique with a sample of 31 people. This study uses primary data or data obtained directly from the object of research by distributing anxiety questionnaires, namely Hamilton Rating Scale For Anxiety (HARS) and therapeutic communication questionnaires which were analyzed using statistical analysis applications, namely SPSS for windows with Chi-Square test. Result: The results of the study obtained respondents who obtained the following results from 31 respondents who received good therapeutic communication, namely 19 respondents (61.3%) and those who received poor communication were as many as 12 respondents (38.7%). Of the 19 respondents who received therapeutic communication (61.3%) of them there was no anxiety as many as 11 people (57.9%) and of the 12 respondents who received poor therapeutic communication, there were 3 respondents (25.0) who had severe anxiety. Based on table 2.4, the chi-square results show p-value = 0.081 > (0.05). Conclusion: based on research that has been done the results obtained show that the relationship between therapeutic communication and anxiety in rheumatic patients at the Jatinagara community health center is not effective.